The Impact of E-learning on Students’ Academic Performance in Indonesian Language Subject - Ida Ayu Maharani; I Gusti Agung Vony Purnama; Ni Kadek Sintya Cahyani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
Many universities, including ITB STIKOM Bali, have adopted e-learning platforms. During the pandemic, e-learning usage expanded significantly; following the epidemic, hybrid learning has been made possible (online and offline). Research on student academic performance is crucial to determining the efficacy of the new online adaptation of remote learning. This descriptive qualitative study intends to highlight how e-learning is used to improve academic performance as well as the difficulties associated with it. ITB STIKOM Bali students were surveyed and interviewed to gather the data. The TAM (Technology Acceptance Model) theory was then used to assess the data that had been collected. The results showed that ITB STIKOM Bali e-learning platform has fulfilled two aspects of the TAM theory, the perception of usefulness and the perception of user convenience which has helped students in improving their academic performance. Meanwhile, some challenges of using e-learning were also experienced by students such as network problems and inability to access e-learning few times.